Review of Cash Flow Statement of Selected Companies of Steel Industry (Tata Steel and Sail) - Abdulkareem, Ahmed Mahdi; Vithalbhai, Vasani Sureshbhai (Journal La Bisecoman, 2021)
The main objective of this study is to assess the ability of the enterprise to generate cash and cash equivalents of the industry. The researcher has selected two companies on the basis of the judgemental sampling method and the researcher has used for the data analysis like mean, trend analysis, and pair “t” test. The researcher has found out the review of the cash flow statement of TATA Steel and SAIL shows the cash inflow and cashes outflow of both the companies, which represents similar solvency and liquidity of both the companies. Thus, investors can invest in both companies because both companies have a sound cash position. So, it should be easy to identify the best investment option for investors. The cash flow statements of the selected two industries of steel sectors have been analysed using different parameters. The selected steel industries are TATA Steel and Steel Authority of India Limited (SAIL). The comparative evaluation of the cash flow statement describes the various variables of cash inflows and outflows of cash of both the industries and the similarity in inflows and outflows of cash. There are 12 variables that were very similar and the data of both the industries were available for the study period. From the analysis, it is concluded that both industries have more similarities in the cash inflow and cash outflow of cash flow statement.